Studi Kesalahan Berbahasa: Komentar Netizen pada Salah Satu Unggahan Liputan 6 di TikTok - Selvina Maharani; Fira Deyanti; Syifa Fauziah Rahmah; Rian Dwiyanto; Malena Nurhayati; Hindun Hindun (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Language error analysis is a working procedure to identify language use. In this digital age, humans can communicate through applications or what can be called social media. One of them is TikTok. This research was conducted on one of the Liputan 6 news uploads on TikTok. The purpose of this study is to identify the language skills of netizens in commenting. With this research, the aim is to identify language errors used by netizens to comment such as errors in spelling or errors in the use of grammatical structures. The method used is a qualitative method with a descriptive approach, namely by making observations on the comments of one of the uploads and then recording the language errors found as research data that will be further examined.